Against the universality of categories: India, Japan, and the limits of modern IR theory - Keerthiraj; Sekiyama, Takashi (Frontiers in Political Science, 2025)
What is called “International Relations theory” today is not a science of the international but a provincial theology of Europe, secularized and universalized as global knowledge. Realism, Liberalism, and Constructivism—these are not mere analytical tools, but conceptual residues of a specific historical experience: that of Latin Christendom grappling with its own theological crisis. When these theories are uncritically applied to non-Western contexts, they illuminate some dynamics but systematically misdescribe others, leaving residual variance unexplained. India–Japan relations, we show, are not an anomaly to these theories but a mirror reflecting their epistemic limitations. We do not abandon their insights but relocate them, showing that under specified scope conditions—early institutionalization, normatively costly cooperation, and trust-persistence—they fall short. We argue that the problem lies not with the world but with the conceptual apparatus we use to describe it. Civilizations are not variations on a universal template—they are distinct ways of being in the world. India and Japan engage each other not through abstract ideas of power or liberal values, but through shared memories, affective trust, and experiential continuity. We propose, therefore, not a new theory, but a shift: from theorizing the world as Europe once experienced it, to letting civilizations describe themselves. Only then does IR become global.